2000
DOI: 10.1530/reprod/118.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of pig theca cell steroidogenesis by LH, insulin-like growth factor I and granulosa cells in serum-free culture

Abstract: The regulation of pig theca cell steroidogenesis was studied by the development of a physiological serum-free culture system, which was subsequently extended to investigate potential theca-granulosa cell interactions. Theca cells were isolated from antral follicles 6-9 mm in diameter and the effects of plating density (50-150x10(3) viable cells per well), LH (0.01-1.0 ng ml(-1)), Long R3 insulin-like growth factor I (IGF-I) (10, 100 ng ml(-1)) and insulin (1, 10 ng ml(-1)) on the number of cells and steroidoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
2
10
0
1
Order By: Relevance
“…It has been previously used to assess the viability of porcine oocytes, granulosa and theca cells [50,51]. In the present study, the viability of follicular cells in tissue strips was assessed, respectively, at day 0 and at day 7 of in vitro culture in both fresh and vitrified-warmed groups.…”
Section: Evaluation Of Follicles In Situ With Neutral Redmentioning
confidence: 99%
“…It has been previously used to assess the viability of porcine oocytes, granulosa and theca cells [50,51]. In the present study, the viability of follicular cells in tissue strips was assessed, respectively, at day 0 and at day 7 of in vitro culture in both fresh and vitrified-warmed groups.…”
Section: Evaluation Of Follicles In Situ With Neutral Redmentioning
confidence: 99%
“…The theca pieces were cut into small pieces and enzymatically dispersed using Hank's balanced salt solution supplemented with 20 mM Hepes, 0.5% w/v collagenase type II, 0.1% w/v hyaluronidase type I-S and 5% fetal calf serum in a shaking water bath at 37°C [30]. The digested cell suspension was washed by centrifugation and resuspended in culture medium: DMEM/Ham's F12 with Hepes and sodium bicarbonate supplemented with 3 mM L-glutamine, 4 ng/ml selenium, 2.5 μg/ml transferrin, 0.1% BSA, 100 IU/ml penicillin and 0.1 mg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…50 × 10 3 viable cells in 50 μl aliquots were seeded into each well of a 96-well plate which contained 200 μl of culture medium supplemented with 10 ng/ml bovine insulin, 100 ng/ml Long R3 IGF-1 and 0.01 ng/ml porcine LH (USDA-pLH-B-2). An optimal dose of LR3 IGF-1 (100 ng/ml) used in granulosa cell cultures was also found to be optimal for theca cell function [30], hence the utilization of control cultures with 100 ng/ml LR3 IGF-1. Shores et al [30] observed that a combination of LR3 IGF-1 (100 ng/ml), insulin (10 ng/ml) and LH (0.01 ng/ml) were required to maintain viable thecal cell numbers in vitro .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations